2006
DOI: 10.1038/sj.emboj.7600950
|View full text |Cite
|
Sign up to set email alerts
|

A divergent external loop confers antagonistic activity on floral regulators FT and TFL1

Abstract: The Arabidopsis genes FT and TERMINAL FLOWER1 (TFL1) encode related proteins with similarity to human Raf kinase inhibitor protein. FT, and likely also TFL1, is recruited to the promoters of floral genes through interaction with FD, a bZIP transcription factor. FT, however, induces flowering, while TFL1 represses flowering. Residues responsible for the opposite activities of FT and TFL1 were mapped by examining plants that overexpress chimeric proteins. A region important in vivo localizes to a 14-amino-acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
535
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 463 publications
(556 citation statements)
references
References 55 publications
16
535
0
5
Order By: Relevance
“…Indeed, loop 127-150 contains eight charged and eight polar amino acids, as well as two glycines and two prolines of 24 amino acids; Banfield et al (8) have generated crystals of dimeric hRKIP and suggested this loop as a putative dimer interface. Others have reported that differences in this loop region participate in opposing effects on flowering of two proteins in Arabidopsis thaliana with high similarity to RKIP (48). Our results, these observations, and the fact that the loop is highly conserved among mammalian RKIP isoforms (12) all suggest that this loop plays an important role in the regulation of protein interactions of RKIP.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, loop 127-150 contains eight charged and eight polar amino acids, as well as two glycines and two prolines of 24 amino acids; Banfield et al (8) have generated crystals of dimeric hRKIP and suggested this loop as a putative dimer interface. Others have reported that differences in this loop region participate in opposing effects on flowering of two proteins in Arabidopsis thaliana with high similarity to RKIP (48). Our results, these observations, and the fact that the loop is highly conserved among mammalian RKIP isoforms (12) all suggest that this loop plays an important role in the regulation of protein interactions of RKIP.…”
Section: Discussionsupporting
confidence: 76%
“…Genetic redundancy, their similar positions to HaFT1 in the flowering time regulatory network, and their molecular mode of action all may have primed HaFT2, HaFT4, and HaTFL1 to respond most appropriately. Both FT and TFL1 homologs interact with FD in other organisms (Pnueli et al 2001;Abe et al 2005;Wigge et al 2005), and it has been hypothesized that phenotypic effects of these genes on flowering and growth depend on the outcome of competitive interactions between members of this family (Ahn et al 2006;Shalit et al 2009;Krieger et al 2010). Increased expression of HaFT2 and HaFT4 are consistent with this scenario, particularly since there is evidence that HaFT2's elevated expression level is controlled by differences in cis-regulatory elements (Blackman et al 2010).…”
Section: Discussionsupporting
confidence: 65%
“…It then moves as a protein from the leaf to the shoot apical meristem through plasmodesmata and the sieve element system (for review, see Turck et al, 2008). FT is a member of the phosphatidylethanolamine-binding protein (PEBP) family with a tertiary structure similar to that of mammalian PEBPs (Ahn et al, 2006). FT is a coregulator of transcription and likely does not function without a TF partner.…”
Section: Stsp6a An Ft Ortholog Of Potato Is a Signal For Tuberizationmentioning
confidence: 99%